Evaluation of efficiency and technological bias of tourist hotels by a meta-frontier DEA model. Issue 5 (3rd May 2020) - Yu, Ming-Miin; Chen, Li-Hsueh
Abstract: Tourist hotels may face different production frontiers and bias of technology between the group frontier and meta-frontier due to technological heterogeneity. This paper develops a meta-frontier data envelopment analysis framework for evaluating the efficiency and technological bias of tourist hotels. By comparing the curvatures of the group frontier and meta-frontier, the relative technological bias between a specific group and the whole industry can be obtained. Furthermore, by investigating the relative technological bias, the direction of technological improvement needed for individual hotels can be ascertained. The proposed method is applied in an empirical example of Taiwanese tourist hotels. The results indicate that most hotels have technological bias and should adjust the curve of their production possibility frontier to match the meta-technology.